Makna Simbolik dalam Tradisi Toron Tana di Desa Bataan Kecamatan Tenggarang Kabupaten Bondowoso - Yusril Satriyo Ihlasul Amal; Maulfi Syaiful Rizal (Student Research Journal, 2023)
This research was prepared with the author's interest in knowing the symbolic meaning in the implementation of the toron tana tradition in Bataan Village, Tenggarang District, Bondowoso Regency. The toron tana tradition is still carried out and maintained by the people of Bataan Village to this day. This tradition is inherited from the ancestors of the Bataan Village community. This research is a type of field research using a qualitative approach, the subjects of this research are the local natives of Bataan Village, Tenggarang District, Bondowoso Regency. Methods of data collection is done by observation, interviews and documentation. Data analysis used is data reduction, data presentation, and verification or drawing conclusions. The results of the study found that the understanding of the people of Bataan Village, Tenggarang District about the toron tana tradition is a ceremonial custom that must be carried out by the local community which is intended to be grateful for the blessings given by God, namely in the form of children who are born safely, healthy until the phase when children begin to learn to walk. The meanings of the symbols used in the Toron Tana Tradition are stepping on jadah, stepping on the ground, entering the chicken coop, and selecting the objects provided in the chicken coop. The meaning of the Toron Tana tradition has the meaning of forming children's character and a positive value for the good of children from parents in achieving goals, having a social spirit and teaching children about gratitude to God.